2020
DOI: 10.3390/nu12082345
|View full text |Cite
|
Sign up to set email alerts
|

The Facts about Food after Cancer Diagnosis: A Systematic Review of Prospective Cohort Studies

Abstract: Nutritional guidelines suggest specific energy and protein requirements for patients with cancer. However, cancer patients, often malnourished, use self-made or web-based diets to ameliorate the prognosis of their disease. This review aimed to investigate the associations between post-diagnostic diet and prognostic outcomes in cancer patients. A systematic literature search was performed in Pubmed and Web of Science databases from inception to 30 October 2019, based on fixed inclusion and exclusion criteria. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
1
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 84 publications
(277 reference statements)
1
20
1
1
Order By: Relevance
“…Regarding dietary intake, breast cancer patients reported that they have a relatively low-fat diet with regular consumption of fiber such as vegetables and high-quality protein intake. This kind of diet is reported in other studies as beneficial and high consumption of saturated fats could be associated with a higher risk of mortality [ 35 ]. A systematic review from 2020 shows that the low-fat diet and healthy quality diet should be recommended but none of the food categories (meat, dairy products) should be eliminated in cancer patients’ diet [ 35 ].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Regarding dietary intake, breast cancer patients reported that they have a relatively low-fat diet with regular consumption of fiber such as vegetables and high-quality protein intake. This kind of diet is reported in other studies as beneficial and high consumption of saturated fats could be associated with a higher risk of mortality [ 35 ]. A systematic review from 2020 shows that the low-fat diet and healthy quality diet should be recommended but none of the food categories (meat, dairy products) should be eliminated in cancer patients’ diet [ 35 ].…”
Section: Discussionmentioning
confidence: 94%
“…This kind of diet is reported in other studies as beneficial and high consumption of saturated fats could be associated with a higher risk of mortality [ 35 ]. A systematic review from 2020 shows that the low-fat diet and healthy quality diet should be recommended but none of the food categories (meat, dairy products) should be eliminated in cancer patients’ diet [ 35 ]. The BC patients in our study also reported that they eat meat every week, but not daily.…”
Section: Discussionmentioning
confidence: 94%
“…Higher all-cause mortality was also reported for lower milk intake [ 48 ]. A low animal protein intake could result in loss of muscle mass, which could worsen clinical outcomes and increase mortality risk [ 49 , 50 ]. Taken together, emerging evidence seems to indicate low fruit and vegetable intake is associated with higher all-cause mortality, especially among colon cancer survivors.…”
Section: Discussionmentioning
confidence: 99%
“…and they revealed a positive tendency in their nutrition intake (such as an increase in the consumption of fruits, vegetables, whole grains) in order to both contribute to the treatment process and reduce the risk of recurrence. (Brennan et al, 2017;Gavazzi et al, 2018;Rinninella et al 2020;Shi et al, 2020). On the other hand, following applications such as chemotherapy, malnutrition can also be seen in patients due to symptoms such as anorexia, nausea-vomiting, fatigue and mucositis, and the individual has to make a forced change in their eating habits.…”
Section: Introductionmentioning
confidence: 99%